Kedudukan Hak Atas Lingkungan Hidup Yang Bersih, Sehat, dan Berkelanjutan dalam Sistem Hukum Indonesia - Sumartini, Ni Wayan Eka; Susilawati, Natalia; Cristiana, Edelweisia; Dewi, Ni Putu Paramita (Satya Dharma : Jurnal Ilmu Hukum, 2025)
Environmental issues have become a global concern, including in Indonesia. One of the critical issues is the right to a clean, healthy, and sustainable environment, which is recognized as part of human rights under the Indonesian legal system. This right is explicitly stated in Article 28H paragraph (1) of the 1945 Constitution and further reinforced by Law Number 32 of 2009 concerning Environmental Protection and Management. However, in practice, the implementation of this right faces various challenges, including weak law enforcement, environmental degradation due to industrial activities, and the criminalization of environmental defenders. This research to analyze the legal standing of the right to a clean, healthy, and sustainable environment within Indonesia's legal system and to emphasize its recognition as a justiciable legal right. The research uses a normative legal method with a literature-based approach by exploring legal sources relevant to the issue. The findings indicate that the government has made efforts to fulfill this right through public education and the formulation of legal instruments. Nevertheless, these efforts remain insufficient to provide comprehensive legal protection. Therefore, there is a need to strengthen normative and institutional aspects and to enhance public participation to ensure the fulfillment of environmental rights as enforceable legal rights. Additionally, the formulation of supplementary regulations is necessary to reinforce existing laws and ensure environmental sustainability for future generations.